An experimental and theoretical study of an efficient polymer nano-photocatalyst for hydrogen evolution. Issue 6 (26th May 2017) - Pati, Palas Baran; Damas, Giane; Tian, Lei; Fernandes, Daniel L. A.; Zhang, Lei; Pehlivan, Ilknur Bayrak; Edvinsson, Tomas; Araujo, C. Moyses; Tian, Haining
Abstract : An organic polymer nano-photocatalyst has been developed for highly efficient light driven proton reduction. Abstract : In this work, we report a highly efficient organic polymer nano-photocatalyst for light driven proton reduction. The system renders an initial rate of hydrogen evolution up to 50 ± 0.5 mmol g −1 h −1, which is the fastest rate among all other reported organic photocatalysts. We also experimentally and theoretically prove that the nitrogen centre of the benzothiadiazole unit plays a crucial role in the photocatalysis and that the Pdots structure holds a close to ideal geometry to enhance the photocatalysis.